Edukasi Bahaya Penyalahgunaan Obat Tramadol dan Triheksifenidil sebagai Upaya Pencegahan Kecanduan pada Remaja SMA di Desa Cihawuk: Pengabdian - Rizqi Indra Hartanto; Eklyn Naiyazalwa Nandhitya; Sani Asmi Ramdani Lestari; Alvira Andrea Jati; Restu Gani; Adhit Rifki Hudaya Nuryadin; Salsabila Fauzia Khaerani; Muhamad Pijar Nur Ramdani; Wahidah Nazmi Lailia; Muhammad Ikhbal; Vieka Yassin Azzahra; Sofi Najwati (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The misuse of tramadol and trihexyphenidyl (THD) among adolescents poses a risk of dependence and health problems. This study aims to provide education about the dangers of drug abuse and analyze its effectiveness in increasing the knowledge of high school students in Cihawuk Village. The activity was held on August 19, 2025, with a one-group pre-test and post-test design. Twenty students joined in the pre-test, followed by an interactive lecture and leaflet distribution as reference material, and then the post-test. The instrument, consisting of 10 questions, had undergone validity and reliability testing, with a Cronbach's Alpha value of 0.700. The results showed that the average pre-test score of 53.50 increased to 81.50 on the post-test (an increase of 52.34%). The Wilcoxon test results showed a Z value of -3.763 with p= 0.000 (p< 0.05), indicating a significant difference between the pre-test and post-test results. Education using lectures and leaflets proved to be effective in increasing adolescents' knowledge about the dangers of drug abuse.